From the Editors - Rynes, Sara (Academy of Management Journal, 2002)
A letter from one of the associate editors is presented. The editor discusses the importance of the social contributions of articles submitted for review by the editors of the periodical. She examines several reasons why some articles are rejected, such as low incremental contribution, overly narrow contribution, and unclear importance, and mentions some ways that authors can enhance their potential contribution.